2015
DOI: 10.3109/1547691x.2015.1017061
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants inTNFα,TGFB1, PTGS1andPTGS2genes are associated with diisocyanate-induced asthma

Abstract: Diisocyanates are the most common cause of occupational asthma, but risk factors are not well defined. A case-control study was conducted to investigate whether genetic variants in inflammatory response genes (TNFα, IL1α, IL1β, IL1RN, IL10, TGFB1, ADAM33, ALOX-5, PTGS1, PTGS2 and NAG-1/GDF15) are associated with increased susceptibility to diisocyanate asthma (DA). These genes were selected based on their role in asthmatic inflammatory processes and previously reported associations with asthma phenotypes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 79 publications
(84 reference statements)
1
24
1
2
Order By: Relevance
“…Previous research has indicated that AKT1 is related to pathway mechanisms in children with severe asthma [ 33 ]; IL6 polymorphisms are related to the effects of smoking on the risk of adult asthma [ 34 ]; VEGFA rs833069 SNPs are associated with asthma [ 35 ]; VEGFA is associated with the response to inhaled corticosteroids in children with asthma [ 36 ]; smoking aggravates airway inflammation by activating the c -Jun amino terminal kinase pathway in asthma [ 37 ]; EGFR activation-induced decreases in claudin 1 promote MUC5AC expression and exacerbated asthma in mice [ 38 ]; the EGRF-dependent signaling pathway is associated with diseases, such as asthma [ 39 ]; neutrophils release CXCL8, NE, and MMP-9 in response to viral surrogates with R848-induced CXCL8 release being specifically enhanced in neutrophils in asthma [ 40 ]. CASP3 may play a role in allergic asthma [ 41 ]; the PTGS2 gene is associated with diisocyanate-induced asthma [ 42 ]. The relationships between these key targets and CVA, some of which have been well studied, could be further studied, and possible mechanisms that have not been previously studied could be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that AKT1 is related to pathway mechanisms in children with severe asthma [ 33 ]; IL6 polymorphisms are related to the effects of smoking on the risk of adult asthma [ 34 ]; VEGFA rs833069 SNPs are associated with asthma [ 35 ]; VEGFA is associated with the response to inhaled corticosteroids in children with asthma [ 36 ]; smoking aggravates airway inflammation by activating the c -Jun amino terminal kinase pathway in asthma [ 37 ]; EGFR activation-induced decreases in claudin 1 promote MUC5AC expression and exacerbated asthma in mice [ 38 ]; the EGRF-dependent signaling pathway is associated with diseases, such as asthma [ 39 ]; neutrophils release CXCL8, NE, and MMP-9 in response to viral surrogates with R848-induced CXCL8 release being specifically enhanced in neutrophils in asthma [ 40 ]. CASP3 may play a role in allergic asthma [ 41 ]; the PTGS2 gene is associated with diisocyanate-induced asthma [ 42 ]. The relationships between these key targets and CVA, some of which have been well studied, could be further studied, and possible mechanisms that have not been previously studied could be explored.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Genetic association studies of diisocyanate-exposed workers, including 2 genome-wide association studies (GWASs), have identified DA-associated genetic variants from multiple loci, some reaching genome-wide significance. [13][14][15][16][17][18][19][20][21] A potential study limitation is the small number of workers with DA able to be recruited (a relatively rare disorder). In the latter publications 19,20 a very well-defined disease phenotype of OA confirmed by using controlled specific inhalation challenge (SIC) testing with the work-relevant isocyanate chemical could explain the large number of reported disease-associated single nucleotide polymorphisms (SNPs).…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…In the latter publications 19,20 a very well-defined disease phenotype of OA confirmed by using controlled specific inhalation challenge (SIC) testing with the work-relevant isocyanate chemical could explain the large number of reported disease-associated single nucleotide polymorphisms (SNPs). DA-associated SNPs have been found in genes encoding antioxidant enzymes, 13,21 HLA class I and II molecules, 18 T H 1/ T H 2 cytokines and CD14, 14,16 and epithelial junctional proteins. 22 Previously, we replicated DA associations with 2 CTNNA3 (a-T catenin) SNPs previously reported in a GWAS of Korean workers.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…подавляет аллергическое воспаление [10]. Однако в ряде работ показано повышение содержания и активности цитокина ТGF-β1 у больных БА, особенно после контакта с аллергеном, что ведет к увеличению количества воспалительных клеток в бронхах [18]. ТGF-β1 действует также на фибробласты, эндотелиальные клетки и гладкую мускулатуру дыхательных путей и способствует формированию ремоделирования дыхательных путей при БА [17].…”
Section: Introductionunclassified